Dealing with elite sport competition demands: an exploration of the dynamic relationships between stress appraisal, coping, emotion, and performance during fencing matches - Doron, J.; Martinent, G. (Cognition and Emotion, 2021)
The present research aimed to provide a more holistic analysis of stressful experiences in sport by examining how stress appraisal, coping and emotion are dynamically inter-related constructs and the extent to which their dynamic relationship is associated with objective performance. Based on process-oriented methods, two studies were conducted with elite athletes in order to investigate the dynamic relationship between these constructs and performance in highly demanding sport situations (Study 1: simulated competitive fencing matches during a training session; Study 2: real-life competitive fencing matches during an international competition). The results of the random coefficient regression models emphasise the dynamic nature of the relationship between stress appraisal, coping behaviour, emotion and objective performance over the course of fencing matches. They allowed identification of additional mediating effects of coping and emotion within dynamic relationships between stress appraisal and performance. These studies contribute to a deeper understanding of psychological adaptation in performance environments. The implications of the findings are discussed in relation to the design of effective coping interventions to support the learning of performance-related coping skills and the attainment of performance goals among individuals in highly demanding environments.